Reflection on Action: Enhancing Preservice Teacher Teaching Performance through Video-based Reflections during Teaching Practicum - Ria Widhiastuti; Teguh Sulistyo; Siti Mafulah; Romia Hari Susanti; Dwi Agus Setiawan; Komm Pechinthorn (Pedagogy Review, 2026)
The transition from preservice to professional teacher requires more than theoretical mastery, but demands reflective engagement with actual classroom practice. This paper discusses how video-based reflection in teaching practicum enhances preservice teacher professional quality. Twenty-five preservice teachers in a micro-teaching program underwent a guided intervention in the form of video-recorded lessons, guided reflection, and semi-structured interviews. Data were thematically analyzed using NVivo. The findings showed that video reflection supported three dimensions of professional growth: skills development, identity formation, and confidence building. Participants moved from surface level consciousness of anxiety, classroom management issues, and teaching shortcomings to tangible improvement plans such as media redesign, rehearsal, and language enhancement. Video recordings provided substantial evidence connecting theory and practice to promote a growth mindset and long-term professional goals. These results underscore the value of incorporating guided video reflection within teacher education curricula as a transformative approach to building reflective practices and to advancing preservice teacher journey toward professionalization. It implies that professional development takes time and deep reflection which preservice teachers have to do as their trajectories before being good teachers in the future. Ultimately, self-reflection, when supported by video-based and guided reflection, can transform performance episodes into meaningful pathways for developing teaching proficiency.